Chemical characteristics of the silage of rachis of banana (Musa paradisiaca) and baby banana (Musa acuminata AA) treated with whey and urea - Caicedo, Willan (2020)
The chemical characteristics of a silage of banana (Musa paradisiaca) and baby banana (Musa acuminata AA) rachis treated with whey and urea were evaluated. In total, 24 microsilos of 1 kg capacity were prepared and the pH, dry matter (DM), crude protein (CP), crude fiber (CF), ashes, ether extract (EE), nitrogen-free extracts (NFE) and gross energy (GE) were determined at 0, 1, 4, 8, 15 and 30 days of conservation (four microsilos for each day). The silage material presented an adequate pH and produced significant increases in the content of DM, CP, ash, EE, NFE and GE and a reduction in the content of CF, with respect to the rachis in its natural state. There was an absence of Escherichia coli, Clostridium spp and Salmonella spp. Mild and strong acid odor, light and dark brown color and solid and semi-solid consistency were evident. The use of drying material, molasses, urea and whey allowed to improve the nutritional composition of plantain and banana rachis, generating a feed of appreciated nutritional quality for use as animal feed.